2017
DOI: 10.1093/bja/aex191
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of perineural vs systemic dexamethasone to prolong analgesia after peripheral nerve block: a systematic review and meta-analysis

Abstract: Perineural dexamethasone has gained popularity in regional anaesthesia to prolong the duration of analgesia, but its advantage over systemic administration is disputed. The objective of this meta-analysis was to compare the analgesic efficacy of both routes of administration during peripheral nerve block. The methodology followed the PRISMA statement guidelines. The primary outcome was the duration of analgesia analysed according to the type of local anaesthetic administered (bupivacaine or ropivacaine). Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 29 publications
(23 reference statements)
4
109
0
3
Order By: Relevance
“…The reduction in the morphine consumption during the 24-48-h interval in favour of the PECS-2 group should be interpreted with caution as it is a secondary outcome and as the duration of the local anaesthetics is not expected to last more than 24 h, even if combined with i.v. dexamethasone [12]. A possible mechanism might be secondary hyperalgesia [17,18], but this needs further research to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…The reduction in the morphine consumption during the 24-48-h interval in favour of the PECS-2 group should be interpreted with caution as it is a secondary outcome and as the duration of the local anaesthetics is not expected to last more than 24 h, even if combined with i.v. dexamethasone [12]. A possible mechanism might be secondary hyperalgesia [17,18], but this needs further research to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, one recently published systematic review evaluated the effectiveness of perineural dexamethasone via systemic administration to prolong analgesia after a peripheral nerve block. The review included 11 studies with 914 participants and the review showed that bupivacaine combined with perineural dexamethasone could provide a longer duration of analgesia compared with systemic dexamethasone (4 hours, P < .0001) …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, another systematic review evaluated the safety of perineural and systemic dexamethasone. Side effects including subsequent infection, hyperglycemia, and neurotoxic effects in these 2 groups were comparable, which were similar to the result of our analysis. So we conclude that a single dose of dexamethasone (<5 mg/kg) is likely safe in terms of postoperative surgical complications regarding wound healing, dehiscence, or infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baeriswyl claims in his recent meta-analysis ‘moderate evidence that perineural dexamethasone combined with bupivacaine, but not ropivacaine , slightly prolongs the duration of analgesia’ 7. Chong meta-analysis suggests that ‘perineural dexamethasone prolonged the duration of analgesia….compared with intravenous dexamethasone, with high statistical heterogeneity ’ 8.…”
mentioning
confidence: 99%